PENERAPAN MEDIA OPEN THE BOX UNTUK MENINGKATKAN KEAKTIFAN BELAJAR PENDIDIKAN PANCASILA SISWA KELAS IV SD KRISTEN PATTI - Kwuwulay, Hermina; Watloly, Aholiab; Kilikily, Cristianti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study uses the Classroom Action Research (CAR) method. CAR focuses on the class and the process of teaching and learning activities that occur in the classroom conducted by teachers and students. The subjects of this study are students of the fourth grade at Christian Elementary School in Patti, Moa District, Southwest Maluku, with a total of 17 students, consisting of 11 male students and 6 female students. This research uses 2 cycles, namely cycle 1 and cycle 2, with data collection techniques in the form of observation, tests, and documentation. The data analysis techniques used are qualitative in the form of field observations and documentation, and quantitative in the increase of student learning outcomes in accordance with the Minimum Completion Criteria (KKM) for the subject of Pancasila Education, which is 70. Based on the results obtained, students are said to be successful as they can meet the KKM for the subject with the following details; 3 students achieved a score of 80 (29.63%), 1 student achieved a score of 90 (33.33%), 13 students obtained a score of 100 (37.04%). The average score in cycle II is 95.88%.